Worldwide innovation and technology environments: Research and future trends involving open innovation - Ismael Cristofer Baierle; Julio Cezar Mairesse Siluk; Vinícius Jaques Gerhardt; Cláudia de Freitas Michelin; Alvaro Luiz Neuenfeldt Júnior; Elpidio Oscar Benitez Nara (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Innovation environments are places where open innovation and technology are boosted. The purpose of this paper is to present the evolution of innovation and technology environments through the most covered topics in the scientific literature. In this sense, technology transfer has been the subject of research since 1975; however, in the period from 2006-2021, the focus shifted to innovation. It was possible to observe an exponential growth of the term, "innovation", but it is no longer the central theme and is linked to different terms related to different ways of innovating, characterizing open innovation variables. In this article, 4650 academic studies involving innovation environments were reviewed. The analysis identified the nomenclatures that characterized innovation environments and the particularities of these environments. The contributions, such as which countries developed more research in this area, and the analysis of which environments were more common in these countries were also presented. Additionally, some methodological and theoretical gaps in the current research were identified, providing pathways to support future research and practices seeking a better understanding and development of innovation environments. This article can also serve as a basis for a consultation for members of the quadruple helix, who wish to install or create environments for innovation and attract companies or investments to develop any open innovation activity.
Keywords: 650; open innovation; innovation ecosystem; innovation environment; technology transfer